The first species of Homaeotarsus Hochhuth, 1851 (Coleoptera: Staphylinidae: Paederinae) with remarkable sexual dimorphism - Cavalcanti, Letícia; Gouvea, Bruno; Valente, Roberta M.; Asenjo, Angélico (Zootaxa, 2026)
Homaeotarsus forceps sp. nov. (Coleoptera: Staphylinidae: Paederinae) from the Brazilian Amazon is described and illustrated. The new species is uniquely diagnosed by the male tergum IX, which is modified into a prominent forceps-like structure, a feature absent in all other known Homaeotarsus species. Specimens were collected via canopy fogging on Eschweilera atropetiolata (Lecythidaceae), a noteworthy record as most Homaeotarsus species are typically associated with leaf litter. Discovered in the Urucu petroleum province (Amazonas State), H. forceps sp. nov. brings the total number of species recorded from Brazil to three and becomes the third known representative of the genus in the Amazon Forest. Additionally, the first identification key to the Brazilian species and a distribution map for South America are provided.